Optimization of Conductive Partitions on the Mixed Convection in a Vented Cavity - Ugurlubilek, Nihal; Sert, Zerrin; Selimefendigil, Fatih; Öztop, Hakan Fehmi (Wiley, 2025)
Numerical estimation for the impacts of the conductive partitions having different positions on the mixed laminar convection of air in a 2D vented enclosure was examined. The variable parameters are accepted as Reynolds number (Re = 10-1000), Richardson number (Ri = 0-5), and size of the partition (0.25H, 0.5H, and 0.75H). Twelve cases having several partition arrangements were analyzed. It was observed that excellent convection control can be obtained by using conductive partitions depending upon the Re and Ri combinations. Generally, at small Re, the mean Nu was not affected by the variation of geometry and Ri at small Re. The highest Nu is achieved in Case 12, a cavity with two partitions having a length of 0.75. At Re = 1000, the rate of increase in Nu at Ri = 0, 1, and 5 are obtained at 2.085, 1.868, and 1.43 according to the bare cavity, respectively. In addition, the effect of the solid-fluid thermal conductivity ratio (K = 0.002, 0.2, 1, 5, and 40) on heat transfer was investigated for Case 12. Empirical power-law Nusselt number correlation was derived for a 2D vented cavity with/without conductive partitions. In conclusion, the maximum heat transfer enhancement rate is obtained in the vented cavity with two length partitions of 0.75. At Re = 1000, the increases in heat transfer rate (Nu/Nu0) for Ri = 0, 1, and 5 are 2.085, 1.87, and 1.43 times higher, respectively, compared with the bare cavity. In terms of effectiveness, Case 12 is the optimum case after Case 0.
Keywords: conductive partition; heat transfer; laminar flow; mixed convection; optimization; vented cavity